67-(4x+11)=4(x+5)+x

Simple and best practice solution for 67-(4x+11)=4(x+5)+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 67-(4x+11)=4(x+5)+x equation:


Simplifying
67 + -1(4x + 11) = 4(x + 5) + x

Reorder the terms:
67 + -1(11 + 4x) = 4(x + 5) + x
67 + (11 * -1 + 4x * -1) = 4(x + 5) + x
67 + (-11 + -4x) = 4(x + 5) + x

Combine like terms: 67 + -11 = 56
56 + -4x = 4(x + 5) + x

Reorder the terms:
56 + -4x = 4(5 + x) + x
56 + -4x = (5 * 4 + x * 4) + x
56 + -4x = (20 + 4x) + x

Combine like terms: 4x + x = 5x
56 + -4x = 20 + 5x

Solving
56 + -4x = 20 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
56 + -4x + -5x = 20 + 5x + -5x

Combine like terms: -4x + -5x = -9x
56 + -9x = 20 + 5x + -5x

Combine like terms: 5x + -5x = 0
56 + -9x = 20 + 0
56 + -9x = 20

Add '-56' to each side of the equation.
56 + -56 + -9x = 20 + -56

Combine like terms: 56 + -56 = 0
0 + -9x = 20 + -56
-9x = 20 + -56

Combine like terms: 20 + -56 = -36
-9x = -36

Divide each side by '-9'.
x = 4

Simplifying
x = 4

See similar equations:

| 4p-9=8(4p-9) | | -4(3-4k)=7k+24 | | 2x=.75 | | (7x-9)+4x=180whatisx | | -3(x+4)=6-4x | | -7-6x=2x+9 | | 3z+16=2z+5 | | -7-6x=-2x+9 | | 16r^2-88r+121=0 | | 5(x+3)+2=-28 | | 3(6t+1)-5=t-(t+1) | | 63=13n+11 | | 2x+y=310 | | (9x-8)(x-7)=0 | | 0.5*p=p+5 | | 4x-9+5x=-45 | | x(5+2x)=3400 | | 6z-3=14 | | 6x+.4=4x | | -2p+2=8 | | 6(4t+1)-12=t-(t+5) | | 2.166666= | | x*(2x+5)=3400 | | 10+5x=8+6x | | 7w=-16+8w | | 18-6x-7=7 | | 6(x+9)=6(x-5) | | 1-3v=-2v+19 | | -4+5x=56 | | 5y^2-11y-4=-13y | | 17z-15z-1=9 | | 32=5n+2 |

Equations solver categories